Assessing the genetic diversity of Alternaria Bataticola in South Africa using molecular markers - Chalwe, Joseph Musonda (Vaal University of Technology, 2015)
Sweetpotato (Ipomoea batatas) is an important food crop that is grown in many countries. A number of viral and fungal sweetpotato diseases have been reported worldwide. One of the major and most economic diseases of the sweetpotato is Alternaria blight which is caused by the fungal pathogen Alternaria bataticola. This disease can be managed in a short term using fungicides and cultural practices. However, a long term and inexpensive approach is through the development of resistant cultivars. A prerequisite to this approach is the knowledge of the genetic diversity of this fungal pathogen. This study assessed the genetic diversity of 25 South African isolates of A. bataticola from naturally infected leaves and stems collected from different sweetpotato growing regions in South Africa by (i) characterising the isolates based on their morphology (ii) pathogenicity tests (iii) random amplified polymorphic DNA (RAPD) (iv) variation of the ITS2 sequences and (v) prediction of the ITS2 secondary structures. The isolates revealed some variation in colony colour pigments after culturing but Koch’s postulates were confirmed by their pathogenicity tests. The analysis of RAPD and variation of the ITS2 sequences showed high levels of variation (100%) among the isolates. Dendrograms generated from these analyses had many subclusters and did not cluster the isolates according to their geographic origins. The ITS2 secondary structures were predicted and can be used to identify and distinguish the isolates. This information in addition to the genetic diversity of the A. bataticola isolates will aid plant breeders in the development of resistant sweetpotato cultivars and early management of blight disease in South Africa.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Sweetpotato; Ipomoea batatas; Sweetpotato diseases; Alternaria blight; Resitant cultivars; 583.94; Sweet potatoes.; Fungi; Dissertations, Academic -- South Africa.